Effects of Different Intensity Exercises On Bone Structure of Young Male Wistar Rats - Filiani Natalia Salim; Hanna Goenawan; Faysal Kastella; Ronny Lesmana; Leonardo Lubis (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Many adolescents have insufficient physical activity. Regular physical activity from young age can improve health and fitness. Getting regular exercise and eating healthy diet should be encouraged among kids and teenagers to prevent various diseases in adulthood and old age, such as osteoporosis and fractures. When exercising, a prescription is needed that is tailored to each individual abilities. The intensity of exercise will be different for each individual in accordance with their age, physiological function, genetics, economic status, and previous comorbid diseases. There is no standardised exercise prescription proven to increase bone mineral density in adolescents. Based on the above description, a study was conducted on the provision of different intensity exercise and its effect on bone morphology and density. In this study, male Wistar rats, aged 15–16 weeks (body weight ± 250-350 grams; n = 20), were split into 4 groups, namely control group, low intensity exercise group, moderate intensity exercise group, and high intensity exercise group. All groups were receiving intervention for 8 weeks. Then, the rats were sacrificed and the femoral bones were isolated. Femur weight and femur length was checked. Bone density was examined using X-Ray and calculated by statistical tests. Research was conducted in the Central Laboratory, Universitas Padjadjaran. There were significant differences of femur weight between high intensity exercise group and control and low intensity exercise groups (p 0.05). Moderate and high intensity exercises significantly increased femur length as opposed to control and low intensity exercise groups (p 0.05). Bone density was higher in moderate and high intensity exercise groups (p 0.05). Moderate to high intensity exercise can increase bone health, seen from significances of bone morphology analysis and a higher density compared to low intensity exercise.